Optical properties of bisacryl‐, composite‐, ceramic‐ resin restorative materials: An aging simulation study. Issue 6 (8th September 2020) - Sulaiman, Taiseer A.; Suliman, Abdulhaq A.; Mohamed, Esraa A.; Rodgers, Brandon; Altak, Ali; Johnston, William M.
Abstract: Objective: Compare optical properties of a bisacryl‐, composite‐, and ceramic‐resin restorative materials pre and post artificial aging. Methods: Bisacryl‐resin (LuxaCrown [LC], DMG), resin‐composite (Filtek Supreme Ultra, [Filtek SU] 3M ESPE), and ceramic‐resin (Enamic, VITA Zahnfabrik) specimens were prepared. The L*, C*ab, and hab values were measured pre and post artificial aging to determine color stability (CIEDE2000) and changes in contrast ratio (CR), transmittance block, and relative translucency parameter. The datasets were analyzed using 2‐way ANOVA followed by pairwise comparisons. Results: Color difference data showed a significant interaction between materials and treatments [F(6:60) = 375.04, P < .0001] with Enamic being most color stable material and coffee having most effect on color stability. CR data showed a significant interaction between materials and treatments [F(6:60) = 4.12, P = .0016]. LC showing most change in CR values with coffee treatment. Change in transmittance blocked by Filtek SU and LC was greater for coffee treatment than that by each of the other treatments ( P < .0001). Filtek SU and LC, coffee produced a greater decrease in relative translucency than that each of the other treatments ( P < .0001). Conclusions: Resin‐based materials demonstrate optical properties that encourage their use for direct/indirect restorative options. Color stability and translucency of these materials are proportionally related. Clinical significance: Understanding the optical properties of resin‐based materials provides help in material selection and provides insight into clinical performance and esthetic longevity. The optical stability of certain bisacryl‐resin is better than what was previously determined for these restorative materials.